2010
DOI: 10.1152/ajpgi.00233.2009
|View full text |Cite
|
Sign up to set email alerts
|

15-Deoxy-Δ12,14-prostaglandin J2 prevents inflammatory response and endothelial cell damage in rats with acute obstructive cholangitis

Abstract: Nakagawa A, Nagino M. 15-Deoxy-⌬ 12,14 -prostaglandin J2 prevents inflammatory response and endothelial cell damage in rats with acute obstructive cholangitis. Am J Physiol Gastrointest Liver Physiol 298: G410 -G418, 2010. First published January 7, 2010 doi:10.1152/ajpgi.00233.2009.-Acute obstructive cholangitis is a common disease with a high mortality rate. Ligands for peroxisome proliferator-activated receptor-␥ (PPAR␥), such as 15-deoxy-⌬ 12,14 -prostaglandin J 2 (15D-PGJ2), have been proposed as a new c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 48 publications
0
4
0
Order By: Relevance
“…PGD 2 is a relatively unstable prostaglandin that has been shown to spontaneously dehydrate to 15-deoxy- Δ 12,14 -PGJ 2 (15d-PGJ 2 ) in vivo and in vitro (Shibata et al , 2002). 15d-PGJ 2 is an anti-inflammatory lipid that mostly mediates its actions directly via activation of PPARγ and/or inhibition of NF-κB signaling in immune cells (Forman et al , 1995; Maggi et al , 2000; Straus et al , 2000; Watanabe et al , 2010). Previous data have shown that PPARγ activation attenuates allergen-induced inflammation in skin and lungs of mice (Dahten et al , 2008; Ward et al , 2006).…”
Section: Discussionmentioning
confidence: 99%
“…PGD 2 is a relatively unstable prostaglandin that has been shown to spontaneously dehydrate to 15-deoxy- Δ 12,14 -PGJ 2 (15d-PGJ 2 ) in vivo and in vitro (Shibata et al , 2002). 15d-PGJ 2 is an anti-inflammatory lipid that mostly mediates its actions directly via activation of PPARγ and/or inhibition of NF-κB signaling in immune cells (Forman et al , 1995; Maggi et al , 2000; Straus et al , 2000; Watanabe et al , 2010). Previous data have shown that PPARγ activation attenuates allergen-induced inflammation in skin and lungs of mice (Dahten et al , 2008; Ward et al , 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Hepatic function was evaluated to compare the results obtained using our AOC animal model with results from previous studies 24 , 25 . ALT, AST, and TBIL levels increased rapidly after BDL compared with those after the sham operation (Table.…”
Section: Resultsmentioning
confidence: 99%
“…The infiltration of immune activated cells is deemed to be associated with bacterial growth in bile and liver extracts that triggers a local and systemic response and induces septicemia, septic shock, and multiple-organ failure, finally resulting in death; this resembles severe acute cholangitis with a high mortality in both humans and mice [ 37 , 38 ]. The reduced expression of pro-inflammatory cytokines, such as IL-1β, IFN-γ and TNF-α, may also reflect the fact that bacterial infection was suppressed in BDL Tg mice [ 12 , 39 ]. A reduced bacterial growth may therefore be the main reason for the lower mortality in Tg mice than in WT mice in the present study.…”
Section: Discussionmentioning
confidence: 99%